Distinctive transcriptome alterations of prefrontal pyramidal neurons in schizophrenia and schizoaffective disorder - Arion, D; Corradi, J P; Tang, S; Datta, D; Boothe, F; He, A; Cacace, A M; Zaczek, R; Albright, C F; Tseng, G; Lewis, D A (Molecular psychiatry, 2015)
Schizophrenia is associated with alterations in working memory that reflect dysfunction of dorsolateral prefrontal cortex (DLPFC) circuitry. Working memory depends on the activity of excitatory pyramidal cells in DLPFC layer 3 and, to a lesser extent, in layer 5. Although many studies have profiled gene expression in DLPFC gray matter in schizophrenia, little is known about cell-type-specific transcript expression in these two populations of pyramidal cells. We hypothesized that interrogating gene expression, specifically in DLPFC layer 3 or 5 pyramidal cells, would reveal new and/or more robust schizophrenia-associated differences that would provide new insights into the nature of pyramidal cell dysfunction in the illness. We also sought to determine the impact of other variables, such as a diagnosis of schizoaffective disorder or medication use at the time of death, on the patterns of gene expression in pyramidal neurons. Individual pyramidal cells in DLPFC layers 3 or 5 were captured by laser microdissection from 36 subjects with schizophrenia or schizoaffective disorder and matched normal comparison subjects. The mRNA from cell collections was subjected to transcriptome profiling by microarray followed by quantitative PCR validation. Expression of genes involved in mitochondrial (MT) or ubiquitin–proteasome system (UPS) functions were markedly downregulated in the patient group ( P -values for MT-related and UPS-related pathways were <10 −7 and <10 −5 , respectively). MT-related gene alterations were more prominent in layer 3 pyramidal cells, whereas UPS-related gene alterations were more prominent in layer 5 pyramidal cells. Many of these alterations were not present, or found to a lesser degree, in samples of DLPFC gray matter from the same subjects, suggesting that they are pyramidal cell specific. Furthermore, these findings principally reflected alterations in the schizophrenia subjects were not present or present to a lesser degree in the schizoaffective disorder subjects (diagnosis of schizoaffective disorder was the most significant covariate, P <10 −6 ) and were not attributable to factors frequently comorbid with schizophrenia. In summary, our findings reveal expression deficits in MT- and UPS-related genes specific to layer 3 and/or layer 5 pyramidal cells in the DLPFC of schizophrenia subjects. These cell type-specific transcriptome signatures are not characteristic of schizoaffective disorder, providing a potential molecular–cellular basis of differences in clinical phenotypes.